Executive Committee Minutes 2018-05-10 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 4/26/18 – Approved. Chair Report. President Report. Special Report – Jacob Yarrow, GMC season. Provost Report. Vice Chair Report. S&F recommendations for semester replacement on URTP for spring 2019, ACIP representative and SSU Enterprises Board – Approved. ICE Guidelines for Faculty. Summer Ex Com quorum confirmed. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Senate Agenda – Approved.